Supply and Demand Analysis of Water Resources based on System Dynamics Model - Huang, Liguo; Yin, Li (Journal of Engineering and Technological Sciences, 2017)
Humans require clean water for industrial, agricultural, domestic and ecological purposes. Due to climate change and population increase, the lack of clean water resources is becoming more and more serious. A system dynamics model of water resources is proposed for alleviating water shortage, changing the imbalance between supply and demand, promoting sustainable patterns of consumption and production, protecting and managing water resources. First, a water supply and demand model combining principles and methods of system dynamics was constructed by analyzing the factors that influence water resources. The model is divided into five subsystems according to the waterâs purpose, i.e. a supply amount subsystem, an industrial water subsystem, an agricultural water subsystem, an ecological and domestic water subsystem, and a sewage water subsystem. In the model, the supply and demand index can indicate whether scarcity occurs as well as the degree of scarcity. The province of Shandong, China was picked as object of research. Relevant statistical data were analyzed to predict the supply and demand index in Shandong in 15 years using the model. Water scarcity in Shandong is explained through social and environmental drivers by addressing physical and economic decline. Finally, an intervention plan was formulated to avoid water shortage from occurring in the next 15 years.